Redescription of Astyanax gymnogenys Eigenmann, 1911 (Characiformes: Characidae), a senior synonym of Astyanax longirhinus Garavello & Sampaio, 2010 - Oliveira, Carlos Alexandre Miranda; Bertaco, Vinícius Araújo; Da Graça, Weferson Júnio; Pavanelli, Carla Simone (Zootaxa, 2019)
Astyanax gymnogenys Eigenmann was described from the middle rio Iguaçu basin, based on two specimens and A. longirhinus Garavello & Sampaio was described from the upper, middle and lower rio Iguaçu, based on several specimens. Due to their morphological similarity, including overlapping diagnostic characters between the two nominal species, allied to their occurrence in the same basin, doubts of their validity as independent taxa emerged. The validity of both taxa was analysed through the examination of type-material of both nominal species and additional material from the rio Iguaçu basin. The present study failed to support the recognition of A. longirhinus as a valid species and consequently, the latter species is herein considered a junior synonym of A. gymnogenys. The type-series of A. longirhinus was found to be composed of several Astyanax species. Astyanax gymnogenys can be differentiated from its congeners occurring at the rio Iguaçu basin by a combination of characters, including presence of vertically-elongated dark humeral blotch, margin of the third infraorbital distant from the margin of preopercle, leaving a broad naked area between these bones more than 25% of the depth of third infraorbital, body deepest at dorsal-fin origin or slightly ahead, and seven to 10 gill rakers on lower arch. We also examined all paratypes of A. scabripinnis paranae from the rio Iguaçu and conclude that they are not conspecific with the holotype, and consequently, that the species does not occur in the rio Iguaçu basin.